Pengaruh Penggunaan Media Pembelajaran Powtoon terhadap Motivasi Belajar Siswa Kelas VII SMP Negeri 1 Tinggi Raja - Putri Ayu Syahfitri; Rusydi Ananda; Ripho Delzy Perkasa (Journal on Education, 2023)
This study aims to determine students' learning motivation in the learning process using powtoon learning media, to determine the implementation of social studies learning using powtoon learning media and to determine the effect of using powtoon learning media on student learning motivation. This research was conducted at SMA Negeri 1 Tinggi Raja, Jalan Danau Teratai, Dusun II Sawah, Tinggi Raja Village, Tinggi Raja District, Asahan Regency, North Sumatra Province. The data collection technique is using internal and external learning motivation questionnaires. Data analysis techniques in this study used descriptive and inferential analysis. Based on the results of the study that obtained a tcount of 1.088 while the ttable value was at a significance level of 5% with N = 60, a ttable of 1.67155 was obtained. The value of tcount < ttable is obtained, namely 1.088 < 1.67155 then Ha is rejected HO is accepted. So it can be concluded that there is no effect of the use of powtoon learning media on the learning motivation of class VII students of SMP Negeri 1 Tinggi Raja